Selected cases of failure analysis and the regulatory agencies in Brazil. Part 1: Aviation, railway and health. (March 2019) - Azevedo, Cesar R.F.; Feller, Achim H.
Abstract: Three cases of failure analysis (aircraft landing gear, cast railway wheel and unalloyed Ti orthopaedic implant) representing three different industry sectors were selected to compose a critical study of their respective regulatory agency in Brazil. The implementation and achieved transparency of the National Civil Aviation Agency (ANAC) for the investigation of aircraft accidents are recognized as state of the art and is consistent with the economic importance of this sector for the country. In contrast, the transparency of the National Land Transportation Agency (ANTT) for the investigation of railway accidents is considered to be deficient. The current organization and transparency of the Brazilian Health Regulatory Agency (ANVISA) for the investigation and prevention of the failure of orthopaedic implants can be criticised as severely flawed. This agency should take immediate actions to adopt the compulsory notification and investigation of the failures of orthopaedic implants and implement a more reliable certification procedure of implants to ensure the protection of the Brazilian health care patients. The transparency of information might play an important role in the trade-off between the independence and the political control of the regulatory agencies in Brazil. In this sense, the publication of conducted failure analyses and general access to their reported findings are seen as a valuable driving force to improve the impact the regulatory agencies have on the general welfare of the country. Highlights: Cases of failure analysis (landing gear, railway wheel and orthopaedic implants) were reviewed. Cases were selected to compose a brief study of their respective regulatory agencies in Brazil. The transparency of these agencies for the investigation of these failures is discussed. The transparency of the regulatory reactions to these failures is discussed.